Impact of Non-Cash Transactions on Household Consumption: Inflation Mediation - Zikri, Adios Amigo; Fadli, Faishal (Contemporary Studies in Economic, Finance and Banking, 2026)
This research examines the influence of non-cash payment instruments on household consumption patterns in Indonesia, while accounting for inflation as an intervening factor. The study employs monthly time-series data covering the period from 2015 to 2024. The analytical framework combines the Autoregressive Distributed Lag–Error Correction Model (ARDL–ECM) to capture both short-run dynamics and long-run relationships, alongside Structural Equation Modeling (SEM) to evaluate the mediating effect. The long-run estimation indicates that transactions conducted through e-money and ATM/debit instruments have a positive and statistically significant impact on household consumption. In contrast, credit card transactions and interest rates do not exhibit significant effects. Inflation is found to significantly influence consumption in the long run and exerts a positive effect in the short run. The ECM results further confirm the presence of a stable adjustment process that restores the system toward long-run equilibrium. Nevertheless, the mediation analysis reveals that inflation does not function as an effective intermediary in the relationship between non-cash payment instruments and household consumption. Overall, the findings suggest that non-cash payment systems affect household consumption predominantly through direct channels rather than indirectly via inflation.